Promising perioperative outcomes of supraclavicular flap in the reconstruction of head and neck complex defects: An evidence-based case report - Fauziah Fardizza; Mirta Hediyati Reksodiputro; Bambang Hermani; Trimartani Koento; Syahrial Marsinta Hutauruk; Dini Widiarni Widodo; Arie Cahyono; Raden Ayu Anatriera; Khoirul Anam (Acta Oto-Laryngologica Case Reports, 2022)
AbstractPedicled flap options have been currently used as a first-line option, especially in developing countries. Several regional flaps are used for complex head and neck (H&N) deformities, such as pectoralis major flap, deltopectoral flap, and forehead flap. Free Tissue Transfer (FTT) is usually used in a large defect that cannot be closed with a regional flap. Recently there has been a resurgence of interest in using cervico-humeral tissue, specifically the supraclavicular flap (SCF). We report one case of pharyngocutaneous fistula following total laryngectomy and neck dissection, which was successfully managed using SCF. Prompted by this case, we present a scoping review of the literature with a specific clinical question, search terms applied, and a critical appraisal was conducted to the selected literature. The finding supports the viability and versatility of SCF as an excellent reliable alternative to FTT and provides evidence for its inclusion in the head and neck reconstructive surgery armamentarium.